Analisis Laju Pertumbuhan Ekonomi, Pengaruh Pertumbuhan Penduduk, dan Upah Minimum Terhadap Tingkat Pengangguran di Provinsi Bali Tahun 2011-2020 - Maria Ayu Emanuelle; I Wayan Wenagama (Jurnal Indonesia Sosial Teknologi, 2022)
The aims of this study are to: (1) identify and analyze the impact of the Economic Growth Rate, Population Growth, and Minimum Wage on unemployment in Bali Province in 2011-2020; (2) and partly on Unemployment in Bali Province in 2011-2020; and (3) identify and analyze the most dominant variables influencing unemployment in Bali Province in 2011-2020. The purpose of this study is to determine and examine the impact of the Economic Growth Rate, Population Growth, and Minimum Wage on unemployment in the Province of Bali in 2011-2020. This research is a quantitative analysis that relies on time series data (2011-2020). For the purposes of this study, secondary data was used. Secondary data is obtained from the Central Bureau of Statistics and periodicals that serve as learning resources. The findings of this study indicate that: (1) population growth has a positive effect on unemployment, the rate of economic growth has a negative effect on unemployment, and the minimum wage has a positive effect on unemployment; (2) The rate of economic growth, population growth, and the minimum wage have a positive effect on unemployment in Bali Province between 2011 and 2020; and (3) Population growth is the dominant variable affecting unemployment.